2018
DOI: 10.1021/acsami.8b04113
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning of Emission Behavior, Self-Assembly, Anion Sensing, and Mitochondria Targeting of Pyridinium-Functionalized Tetraphenylethene by Alkyl Chain Engineering

Abstract: Compared to the many studies that focus on the development of novel molecular frameworks pertaining to functionalized fluorescent materials, there is lesser emphasis on side chains even though they have a significant impact on the properties and applications of fluorescent materials. In this study, a series of pyridinium-functionalized tetraphenylethene salts (TPEPy-1 to TPEPy-4) possessing different alkyl chains are synthesized, and the influence of chain length on their optical performance and applications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 57 publications
0
45
0
Order By: Relevance
“…In addition, some piecemeal reports also indirectly supported the applicability of the SCES we have proposed. [37][38][39] For example, in a previous study, we found that the molecule LAD-1 with methyl always needs a longer time to enter cells in comparison to the molecule LAD with butyl. 36 Moreover, commercial probes such as TMRM and TMRE with two methyls can cross the plasma membrane more rapidly than rhodamine 123 without an alkyl chain.…”
Section: Sces Enables Conversion Of Impermeable Dyes Into Permeable Onesmentioning
confidence: 99%
“…In addition, some piecemeal reports also indirectly supported the applicability of the SCES we have proposed. [37][38][39] For example, in a previous study, we found that the molecule LAD-1 with methyl always needs a longer time to enter cells in comparison to the molecule LAD with butyl. 36 Moreover, commercial probes such as TMRM and TMRE with two methyls can cross the plasma membrane more rapidly than rhodamine 123 without an alkyl chain.…”
Section: Sces Enables Conversion Of Impermeable Dyes Into Permeable Onesmentioning
confidence: 99%
“…Recently, Zhao and Tang et al. reported that changes to the alkyl chain length can be an approach to manipulate the self‐assembly of AIEgens . They synthesized a series of pyridinium‐functionalized TPE salts (TPEPy) with different alkyl chains (Figure ).…”
Section: Endowing Aie Molecules With Self‐assembly Ability Through Momentioning
confidence: 99%
“… Effect of alkyl chain length on the self‐assembly, emission, anion detection, and cell imaging of TPEPy‐ n ( n =1, 4, 7, 10) …”
Section: Endowing Aie Molecules With Self‐assembly Ability Through Momentioning
confidence: 99%
See 2 more Smart Citations